Balance and postural control in basketball players - Murilo Curtolo; Helga Tatiana Tucci; Tayla P. Souza; Geiseane A. Gonçalves; Ana C. Lucato; Liu C. Yi
Abstract Introduction: Basketball is one of the most popular sports involving gestures and movements that require single-leg based support. Dorsiflexion range of motion (DROM), balance and postural control may influence the performance of this sport. Objective: To compare and correlate measures of balance, postural control and ankle DROM between amateur basketball athletes and non-athletes. Methods: Cross-sectional study, composed by 122 subjects allocated into one control group (CG = 61) and one basketball group (BG = 61). These groups were subdivided into two other groups by age: 12-14 years and 15-18 years. The participants were all tested for postural balance with the Star Excursion Balance Test (SEBT), postural control with the Step-down test and DROM with the Weight-bearing lunge test (WBLT). Between-groups differences were compared using repeated-measures multivariate analysis of variance. Normalized reaching distances were analyzed and correlated with the WBLT and Step-down test. Results: There was no difference in the scores of WBLT (P = .488) and Step-down test (P =. 916) between the groups. Scores for the anterior reach (P = .001) and total score of SEBT (P = .030) were higher in BG. The values for the posterolateral (P = .001) and posteromedial reach (P = .001) of SEBT were higher in BG at the age of 15-18. The correlation between the anterior reach of the SEBT and WBLT was significant in BG between 12-14 years (r = 0.578, P = .008), and in the CG between 15-18 years (r = 0.608, P=.001). Conclusion: The balance was better in the BG, although adolescents between 15-18 years have better balance control for the posteromedial and posterolateral reaches of the SEBT.